The language myth why language is not an instinct - Evans, Vyvyan (Cambridge University Press, 2014)
"Language is central to our lives, the cultural tool that arguably sets us apart from other species. Some scientists have argued that language is innate, a type of unique human 'instinct' pre-programmed in us from birth. In this book, Vyvyan Evans argues that this received wisdom is, in fact, a myth. Debunking the notion of a language 'instinct', Evans demonstrates that language is related to other animal forms of communication; that languages exhibit staggering diversity; that we learn our mother tongue drawing on general properties and abilities of the human mind, rather than an inborn 'universal' grammar; and that, ultimately, language and the mind reflect and draw upon the way we interact with others in the world. Compellingly written and drawing on cutting-edge research, The Language Myth sets out a forceful alternative to the received wisdom, showing how language and the mind really work"--Provided by publisher.